2015
DOI: 10.4254/wjh.v7.i25.2563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological significance of precursor lesions of intrahepatic cholangiocarcinoma

Abstract: Cholangiocarcinoma (CC) is primarily a malignant tumor of older adults most prevalent in Southeast Asia, where liver fluke infestation is high. However the etiology in western countries is unknown. Although the incidence of extrahepatic cholangiocarcinoma has remained constant, incidence of intrahepatic CC (ICC) which differs in morphology, pathogenesis, risk factors, treatment and prognosis is increasing. While this increase is associated with hepatitis C virus infection, chronic nonalcoholic liver disease, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 73 publications
1
26
0
2
Order By: Relevance
“…Studies of molecular alteration reported that BilIN showed a step-wise increased expression of oncogene-related molecules such as p21, p53, and cyclin D, and a stepwise decreased expression of Smad4 during the progression of the grades of BilIN [13]. In other studies, Ki67 proliferative index was reported to range from 11 to 84.8% in intrahepatic CC [14,15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of molecular alteration reported that BilIN showed a step-wise increased expression of oncogene-related molecules such as p21, p53, and cyclin D, and a stepwise decreased expression of Smad4 during the progression of the grades of BilIN [13]. In other studies, Ki67 proliferative index was reported to range from 11 to 84.8% in intrahepatic CC [14,15].…”
Section: Discussionmentioning
confidence: 95%
“…Biliary intraepithelial neoplasia (BilIN) is a precursor to both intrahepatic and extrahepatic CC, and it has been associated with several conditions known to predispose to CC [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This method for the detection of CC has a sensitivity of 83% and a specificity of 100% (13,114,115). Screening for the genetic and epigenetic alterations in the precursor lesions, including intraductal papillary neoplasm of the bile duct (IPNB) and biliary intraepithelial neoplasia (BilIN), as discussed by Ettel et al, may also be beneficial (116). The diagnostic and treatment challenges are also due to the heterogeneity of clinical presentations, which may be due to the origin of CC from topographically heterogeneous cholangiocytes.…”
Section: Signal Transducer and Activator Of Transcription 3 (Stat3)mentioning
confidence: 99%
“…However, mucin production is uncommon in IPNB. Pancreatobiliary subtype is the most frequent phenotype in the Western population . Nearly 40% of IPNBs are associated with cholangiocarcinoma, and this is more prevalent in the pancreatobiliary than in other subtypes .…”
mentioning
confidence: 99%
“…Pancreatobiliary subtype is the most frequent phenotype in the Western population. 2 Nearly 40% of IPNBs are associated with cholangiocarcinoma, and this is more prevalent in the pancreatobiliary than in other subtypes. 3 Moreover, synchronous and metachronous lesions are common along the biliary tree in patients with IPNB requiring careful pathological and radiological assessment.…”
mentioning
confidence: 99%